Pengaruh Current Ratio, Debt To Equity Ratio, dan Net Profit Margin Terhadap Roa Pada PT. Semen Indonesia (Persero) Tbk. Tahun 2009-2016 - Khakim, M. Azizul (Yayasan Literasi Sains Indonesia, 2022)
This study aims to analyze the effect of Current Ratio, Debt to Equity Ratio, and Net Profit Margin on Return On Assets at PT. Semen Indonesia (Persero) Tbk. year 2009-2016. This type of research is quantitative associative. The data source is secondary data taken from the official website of Semen Indonesia at www.semenindonesia.com. The research data is in the form of quarterly financial report data of PT. Semen Indonesia (Persero) Tbk. in 2009-2016 as many as 32 financial reports. Analysis of the data used is multiple linear regression analysis. The results showed that the Current Ratio, Debt to Equity Ratio, and Net Profit Margin simultaneously had a significant effect on Return On Assets at PT. Semen Indonesia (Persero) Tbk. in 2009-2016, but partially Current Ratio, Debt to Equity Ratio, and Net Profit Margin have no significant effect on Return On Assets at PT. Semen Indonesia (Persero) Tbk. year 2009-2016. From the results of tcount, it shows that the Net Profit Margin which gives the most dominant influence on Return On Assets.